1997
DOI: 10.1523/jneurosci.17-17-06685.1997
|View full text |Cite
|
Sign up to set email alerts
|

Subunit Composition, Kinetic, and Permeation Properties of AMPA Receptors in Single Neocortical Nonpyramidal Cells

Abstract: Native AMPA receptors (AMPARs) were investigated in neocortical fast-spiking (FS) and regular-spiking nonpyramidal (RSNP) cells. The onset of and recovery from desensitization as well as current rectification and single-channel conductance were studied by using fast glutamate application to outside-out patches. The GluR1-4 subunit, flip/flop splicing, and R/G editing expression patterns of functionally characterized cells were determined by single-cell reverse transcription-PCR to correlate the subunit composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(101 citation statements)
references
References 37 publications
7
94
0
Order By: Relevance
“…AMPA receptor-mediated currents rise and decay faster in interneurons than in principal neurons, in part because of different subunit profiles (30)(31)(32). Electrophysiological studies indicate that, in hippocampus, pyramidal͞interneuron synaptic connections are powerful and elicit action potentials at short latency, even in resting conditions, when only one or a few presynaptic cells fire (19,24).…”
Section: Discussionmentioning
confidence: 99%
“…AMPA receptor-mediated currents rise and decay faster in interneurons than in principal neurons, in part because of different subunit profiles (30)(31)(32). Electrophysiological studies indicate that, in hippocampus, pyramidal͞interneuron synaptic connections are powerful and elicit action potentials at short latency, even in resting conditions, when only one or a few presynaptic cells fire (19,24).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports in rodents (Geiger et al, 1995;Vissavajjhala et al, 1996;Angulo et al, 1997;Kondo et al, 1997) and primates (Vickers et al, 1993;Munoz et al, 1999) suggest that some classes of cortical neurons, including those expressing calcium-binding proteins, can be differentiated by their expression of different AMPA receptor subunits. However, our present experiments revealed that in normal cats, the great majority of calbindin-and parvalbuminpositive cells, and the majority of LS-projecting pyramidal cells in layer II/III of area 18 expressed all four subunits of the AMPA receptor.…”
Section: Expression Of Ampa Receptor Subunits In Supragranular Layersmentioning
confidence: 97%
“…They are comprised of four subunits-GluR1, GluR2, GluR3, and GluR4-that are differentially expressed in different neurons (Vickers et al, 1993;Geiger et al, 1995; Vissavaijhala et al, 1996;Angulo et al, 1997;Kondo et al, 1997;Munoz et al, 1999;Van Damme et al, 2003). Although many glutamate receptors (such as AMPA, N-methyl-D-aspartate [NMDA], kainate) play a role in activity-dependent neuronal plasticity (Collingridge and Singer, 1990;Malenka and Nicoll, 1993), the sensitivity of AMPA receptor to changes in connectivity and function within the cat visual system has been well demonstrated (Gordon et al, 1996;Price and Huxlin, 2001;Van Damme et al, 2003).…”
Section: Indexing Termsmentioning
confidence: 99%
“…In rodents, neocortical pyramidal cells are not directly depolarized by nicotinic agonists (Vidal and Changeux, 1993;Gil et al, 1997) (but see Roerig et al, 1997), suggesting that these non-␣7 nicotinic receptors may be expressed by interneurons. Despite the general use of GABA as a neurotransmitter, neocortical interneurons are widely heterogeneous in terms of morphological, physiological, and biochemical characteristics (McCormick et al, 1985;Kubota et al, 1994;Thomson and Deuchars, 1994;Kawaguchi, 1995;Angulo et al, 1997;Cauli et al, 1997;Porter et al, 1998; Xiang et al, 1998). Therefore, the stimulation of different types of neocortical interneurons can produce a large variety of functional outcomes.…”
Section: Abstract: Single-cell Pcr; Neuropeptides; Calcium-binding Pmentioning
confidence: 99%